Efektivitas Pembelajaran Daring Mata Pelajaran Bahasa Jawa Kelas XI TLAS 2 Semester Gasal di SMK Negeri 1 Jepon - Ariani, Eva; Werdiningsih, Yuli Kurniati; Alfiah, Alfiah (Universitas PGRI Semarang, 2021)
The Covid-19 pandemic has forced the learning system in shools to change drastically from face-to-face meetings to online learning. No exception State Vocational High School 1 Jepon also conducts online learning with various online applications including google classroom, google form, and YouTube. This study aims to analyze the effectiveness of online learning in Javanese language class XI TLAS 2 odd semester at State Vocational High School 1 Jepon. This research is a qualitative descriptive study. Data collection techniques used documentation and questionnaires containing the effectiveness of online learning in Javanese language class XI TLAS 2 odd semester at State Vocational High School 1 Jepon. The study population was all students of State Vocational High School 1 Jepon who were taught in Javanese subjects using online methods. The research sample was students in class XI TLAS 2Â State Vocational High School 1 Jepon. The results showed that online learning was less effective and directly proportional to studentsâ€™ lack of understanding in learning. Online learning in Javanese class XI TLAS 2 odd semester at State Vocational High School 1 Jepon is by using the google classroom application, google form, and YouTube and the learning model is by providing material, observing, then giving assignments by the teacher to students. The media used by students for online learning are gadgets (HP) and the obstacles faced by students in online learning are limited data quotas and slow internet networks.